Peran Kepala Sekolah dalam Meningkatkan Kompetensi Guru di Pondok Pesantren Darunnajah Jakarta - Sofwan Manaf; Rokimin (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2023)
Abstract:All stakeholders in educational institutions, especially teachers during the learning process in class, are responsible for improving teacher competency. Therefore, developing teacher competence is very important which is influenced by several variables, including the role of the principal himself. Based on these problems, the authors wish to conduct research on the role of school principals in improving teacher competency at the Darunnajah Islamic Boarding School, Jakarta. This study aims to identify the variables that can influence the increase in teacher competence as well as the challenges faced and the role of the principal in increasing teacher competency at Pondok Pesantren Darunnajah Jakarta. All principals and deputy principals of the Darunnajah Islamic Boarding School became the population and sample in this study. This research methodology combines qualitative and descriptive approaches. Information is collected by means of observation, discussion, and documentation. The findings of this study indicate that the role of school principals, teacher training, student learning facilities, teacher teaching experience, teacher health conditions, and educational background are factors that influence the increase in teacher competence and the quality of education. Along with the limitations of pedagogical and professional abilities, the principal's responsibility is to improve teacher competency through MGMP empowerment, academic and clinical supervision, as well as face-to-face training with other teachers.